Comparison of Indonesian and European Logistics Competency Frameworks in Supply Chain - Vina Dwiyanti; Ana A; Edi Supardi; Yusep Sukrawan (Jurnal Ketenagakerjaan, 2026)
Rapid advancements in digital technologies, increasing sustainability pressures, and the growing complexity of global supply chains have reshaped the competency landscape for logistics professionals. This study conducts a comparative analysis of transversal skill requirements in the Indonesian logistics sector by benchmarking industry expectations against the existing national competency framework (SKKNI) and the European Logistics Association Qualifications Framework (ELAQF). Drawing on recent literature and industry reports (2022–2025), the findings reveal significant discrepancies across five critical domains: digital, managerial, technical, soft, and green skills. While industry practices increasingly demand integrated system proficiency, analytics-driven decision-making, agile management, and sustainability awareness, SKKNI remains largely procedural, emphasizing manual tasks and basic operational functions. To address these gaps, the study proposes an Integrated Transversal Skills Framework that conceptualizes how the five skill domains collectively enhance employability, workforce agility, and readiness for digital and green logistics transformation. This conceptual model highlights the strategic importance of embedding transversal skills into curriculum design, professional training, and national qualification updates. The study concludes that modernizing Indonesia’s competency standards is essential for strengthening workforce competitiveness and aligning with global logistics trends. Future research should focus on empirical validation of the proposed model and sector-specific assessments across warehousing, transport, and supply chain services.